Effect of strain rate on low cycle fatigue of 316LN stainless steel with varying nitrogen content: Part-II fatigue life and fracture. (December 2015) - Prasad Reddy, G.V.; Mariappan, K.; Kannan, R.; Sandhya, R.; Sankaran, S.; Bhanu Sankara Rao, K.
Graphical abstract: Highlights: Nitrogen in 316LN SS enhances LCF life only if fracture is by transgranular mode. Nitrogen is beneficial up to 0.11–0.14 wt.% in case of transgranular LCF failures. In LCF tests that cause intergranular damage, increase in nitrogen decreases life. Grain boundary yields to intergranular damage by dynamic strain aging and creep. Intergranular triple-point cracking is caused by grain boundary sliding. Abstract: Low cycle fatigue (LCF) life and fracture behavior of 316LN stainless steel with varying nitrogen content (0.07, 0.11, 0.14 and 0.22 wt.%) is studied over a range of strain rates at temperatures 773 K, 823 K and 873 K. Nitrogen content in 316LN SS is observed to play a dual role (detrimental or beneficial) in influencing the fatigue life. An improvement in fatigue life up to 0.11–0.14 wt.% N is observed under the test conditions that promoted transgranular fatigue failure, such as in LCF tests at a strain rate of 3 × 10 −3 s −1 . On the other hand, nitrogen addition induced considerable reduction in fatigue life for the test conditions causing intergranular damage, and accordingly fatigue life decreased with increase in nitrogen content. Intergranular damage in the later case is manifested in the form of triple point cracks and interconnected networks of grain boundary decohesion. The occurrence of intergranular damage is primarily attributed to the detrimental consequences of DSA and creep damage supplemented by oxidation and precipitation effects, in particular for nitrogen contents above 0.07 wt.%.